Cognition, literacy and mobile technology: A conceptual model of the benefits of smartphones for Aboriginal students in remote communities - Johnson, Genevieve; Oliver, Rhonda (AACE, 2013)
Indigenous youth in remote regions of Australia are disadvantaged in school and in life. While the reasons are complex and multi-faceted, improved connectivity infrastructure, hardware such as smartphones and highly motivating Web 2.0 applications may provide mechanisms by which to improve the educational outcomes of Indigenous students in remote communities. Based upon review of the literature, a pedagogical model is proposed and presented. The model organizes the relationships between web-based applications, Indigenous learning styles and life circumstances and the potential benefits of smartphones in terms of cognitive and literacy skills. Smartphones may constitute a particularly powerful mechanism by which to improve the reading skills of Indigenous adolescents living in remote communities. The connectivity infrastructures, sophistication of devices and Indigenous adolescent motivation all currently exist.